Business Analysis of Jakarin 1 Composite Maize Seed Production in Bukit Peninjauan II, Sukaraja District, Seluma Regency - Suci Gustiawan; Edi Efrita; Novitri Kurniati; Edy Marwan (Westscience Press, 2026)
Jakarin 1 composite maize is a superior variety capable of adapting to unfavorable environmental conditions and has high economic potential. This study aimed to analyze profitability, efficiency, feasibility, and the break-even point (BEP) of the Jakarin 1 composite maize seed production enterprise in Bukit Peninjauan II, Sukaraja District, Seluma Regency. The study was conducted from August to November 2024 using a census method involving the entire population of seed breeder farmers (four respondents). Primary data were collected through interviews using questionnaires, while secondary data were obtained from supporting literature. The analyses included income analysis, efficiency ratio (R/C), feasibility ratio (B/C), and break-even point analysis for both production and sales. The results showed that the average total production cost was IDR 10,415,040.87, while total revenue reached IDR 32,756,717.50, resulting in a net profit of IDR 22,341,676.63. The R/C ratio was 2.17 and the B/C ratio was 1.17, indicating that the enterprise is economically efficient and feasible. The break-even point was achieved at a sales volume of 347.17 kg of seed. Therefore, the Jakarin 1 composite maize seed production enterprise has promising prospects to be developed as a main source of farmers’ income.